Dropout in Private Higher Education (Research, Society and Development, 2021)
Dropout in higher education is a topic that has been studied more significantly in recent years. It fits not only in the concern of affirmative policies for student inclusion, but, in particular, of private institutions, considering that they have the highest percentage of students in this situation and, therefore, the main interested in keeping them in their courses. This article, then, has as a general objective to analyze the reasons that lead students to drop out of on-site Higher Education. The methodology used for this research is based on bibliographic and documentary analysis procedures. For this, a digital collection is used, with the aid of the internet, for bibliographical reviews, articles, monographs and dissertations on this subject. The study indicates that the lack of knowledge about the chosen course, uncertainties regarding career possibilities in the area, students' financial difficulties, poor academic performance and the need to articulate time between study and work are among the most cited reasons for dropout in Higher Education. Therefore, in order to work on a dropout reduction project, Higher Education Institutions must make a specific diagnosis of their reality, deeply analyzing the internal and external variables of the institution and its students.